Parkinson's disease genes expression study by QPCR in nitrosative stress induced pc12 cell line (Funded Work) - ANUSHREE,; ARAVIND P,; GIRISHA SHRINGALA THIMAPPA,; DEVARAJU KURAMKOTE SHIVANNA, (International Journal of Pharma and Bio Sciences, 2017)
Nitrosative stress leads to Parkinson’s disease through mitochondrial dysregulation. Although Parkinson’s disease is caused by several genes such as Parkin, DJ-1, PINK1, ATP13A2, PLA2G6, FBXO7, SNCA, LRRK2, VPS35 and GBA but there is a need for the investigation of sensitivity and expression of Parkinson’s disease genes upon nitrosative stress. Hence the current study focused on Parkinson’s disease gene expression in PC12 cells upon nitrosative stress. The nitrosative stress was carried out by rotenone, SIN1 and peroxynitrite and the expression pattern of genes were studied using real time PCR. PTEN-Induced putative kinase 1 (PINK1), Leucine-rich repeat kinase 2 (LRRK2) and Vacuolar Protein Sorting-associated protein 35 (VPS35) genes were analysed by real time PCR. Our findings demonstrate that under nitrosative stress the expression of VPS35 is up regulated by 1.35 fold when treated with lower concentration of peroxynitrite (250 µM); however under higher concentration it is down regulated :10 fold with 1mM peroxynitrite, 16.7 fold with 0.5 µM and 2.5 µM rotenone, 8.3 fold and 7.6 fold with 50 µM and 250 µM SIN1. The PINK1 found to be down regulated: 50 fold with 250 µM peroxynitrite, 20 fold with 1mM peroxynitrite, 14.3 fold with 0.5 µM rotenone, 16.7 fold with 2.5 µM rotenone, 11.1 fold with 50 µM SIN1 and 10 fold with 250 µM SIN1 under all concentrations; surprisingly LRRK2 gene did not show any kind of expression during PCR optimisation itself. In conclusion PINK1 appears to be most sensitive compare to VPS35 as it is down regulated with lower concentration of peroxynitrite.